Herpetofaunal community structure and habitat associations in Gunung Ciremai National Park, West Java, Indonesia - AWAL RIYANTO (Biodiversitas Journal of Biological Diversity, 2011)
Riyanto A (2011) Herpetofaunal community structure and habitat associations in Gunung Ciremai National Park, West Java, Indonesia. Biodiversitas 12: 38-44. Community structure and habitat associations of amphibians and reptiles on both rainy and dry seasons of six habitat types of three sites in Gunung Ciremai National Park, West Java were investigated in March and October 2008. The data of herpetofauna was obtained by opportunistic searches. Herpetofaunal diversity for each habitat was determined by using Shannon Wienerindex, the species abundance per unit area was calculated by using Margalef’s index, and the homogeneity of distribution of species in relation to other species in a sampled per unit area was evaluated using Evenness index. The similarity in herpetofauna communities among habitat types was determined using Sorensen’s coefficient, meanwhile the Jaccard’s index was used to estimate similarities in habitat utilization. Thus, both community similarities and habitat utilization displayed in cluster dendrogram. A total of 46 amphibian and reptile taxa were recorded, comprising 16 anurans, 22 lizards and 8 snakes. Of the total taxa, four anurans are endemic and unusual specimens probably new in sciences referred to the genus Cyrtodactylus and Eutropis. There were differed in sequential of biological indices among habitat types but not much different in their values. The result of cluster analysis showed different patterns on the community similarity among habitat type and habitat utilization during rainy and dry seasons.Key words: community, habitat utilization, amphibians, reptiles, Gunung Ciremai, Indonesia